Policymakers’ Views of Future-Oriented Skills in Science Education - Ioannidou, Olga; Erduran, Sibel (Frontiers in Education, 2022)
The rapid changes in science and society during the last decade have demonstrated the need for readiness to address the uncertain future through the development of future-oriented skills. Despite previous attempts, there is still no consensus regarding what is meant by “future-oriented skills” and how these could be integrated into science curricula. Stakeholders’ views about what future-oriented skills are and how they should be taught would provide a clearer understanding of their needs and their perceived characteristics of effective new teaching approaches. Thus, given the pivotal role that policymakers play in education policies, this study investigated the views of 35 policymakers based in England, Italy, Finland and Lithuania. Participants completed an online survey that elicited their views on future-oriented skills, as well as ways of integrating them into national science curricula. The data analysis included descriptive statistics and qualitative analysis based on the principles of thematic analysis. The qualitative analysis followed a combination of inductive and deductive coding approaches. The findings of this study highlight that among other skills, participants stressed the need for introducing problem-solving and critical thinking in science classrooms in order to better address the uncertainty of future challenges, such as environmental issues. Therefore, policymakers seem to agree that there is a need for moving away from traditional teacher-centred approaches when teaching future-oriented skills. These results provide valuable insights into policymakers’ needs and expectations. In doing so, this study can serve as a starting point for a systematic approach toward integrating future-oriented skills into science curricula.